The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.nedt.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The competence of nurse mentors in mentoring students in clinical practice – A cross-sectional study

Abstract: According to their profiles, mentors have diverse needs for support in building their mentoring competence. We suggest that healthcare organizations should provide nursing mentors with education that is based on their individual levels of mentoring competence. Nurses should also be encouraged to use time for reflective discussion with students during clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 23 publications
(32 reference statements)
4
47
0
1
Order By: Relevance
“…In addition, Meden et al () reported that 58% of mentors included reflection during their mentoring, supported with the ability to use evaluation tools. Other studies also found that mentors regarded their reflection during mentoring (Oikarainen et al, ; Ruuskanen et al, ; Tuomikoski et al, ) and provision of feedback (Oikarainen et al, ; Tuomikoski et al, ) as fairly high.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…In addition, Meden et al () reported that 58% of mentors included reflection during their mentoring, supported with the ability to use evaluation tools. Other studies also found that mentors regarded their reflection during mentoring (Oikarainen et al, ; Ruuskanen et al, ; Tuomikoski et al, ) and provision of feedback (Oikarainen et al, ; Tuomikoski et al, ) as fairly high.…”
Section: Resultsmentioning
confidence: 93%
“…In the studies, mentors' competence was self‐assessed with instruments including: unnamed instruments developed by the authors (Borch et al, ; Hall‐Lord et al, ; Heffernan et al, ; Helminen et al, ; McInnes et al, ; Meden et al, ; Omer et al, ; Skela‐Savič & Kiger, ; Smith et al, ); the Involvement, Motivation, Satisfaction, Obstacles and Commitment Instrument (Cervera‐Gasch et al, ); Mentor´s Competence Instrument (MCI) (Kälkäjä et al, ; Karjalainen et al, ; Oikarainen et al, ; Ruuskanen et al, ; Tuomikoski et al, ) and Nursing Students' Contributions to Clinical Agencies (NSCCA) instrument (Morrison & Brennaman, ). Validated instruments are categorised in terms of competence areas covered in Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations